Perceived organizational politics, organizational disidentification and counterproductive work behaviour: Moderating role of external crisis threats to work - De Clercq, D.; Pereira, R. (International Journal of Organizational Analysis, 2024)
Purpose—This research seeks to unpack the relationship between employees’ perceptions of organizational politics and their counterproductive work behaviour, by postulating a mediating role of organizational disidentification and a moderating role of perceived external crisis threats to work. Design/methodology/approach—The empirical assessment of the hypotheses relies on survey data collected among employees who work in a large banking organization. Findings—Perceptions that organizational decision-making is marked by self-serving behaviour increase the probability that employees seek to cause harm to their employer, because they feel embarrassed by their organizational membership. This mediating role of organizational disidentification is especially prominent when they ruminate about the negative impact of external crises on their work. Practical implications—This study details an important danger for employees who feel upset with dysfunctional politics: They psychologically distance themselves from their employer, which then prompts them to formulate counterproductive responses that likely make it more difficult to take on the problem in a credible manner. This detrimental dynamic is particularly risky if an external crisis negatively interferes with their work functioning. Originality/value—This study adds to prior research by detailing an unexplored but relevant mechanism (organizational disidentification) and moderator (external crisis threats) by which perceived organizational politics translates into enhanced counterproductive work behaviour.